PROBLEM-BASED LEARNING (PBL) PADA TOPIK ASAM BASA : MENINGKATKAN KEMAMPUAN LITERASI PESERTA DIDIK - Sri Setiawaty (Universitas Samudra, 2024)
Meaningful learning in chemistry needs to consider the character of chemical content and students. Problem-based learning (PBL) provides a learning environment that is related to daily life and can support the achievement of meaningful learning for students in chemistry. This research was a best practice research that was implemented in the class XI SMA Negeri 1 Dewantara with a total of 32 students. This research aims to improve students' literacy skills through the application of the PBL’s model. Data collection was carried out using pretest and posttest to determine students' literacy abilities. From the research results, it was found that there was an increase in scores of 76.6%, where the average pretest score was 49.7, increasing to an average posttest score of 87.8. This shows that the application of PBL has a better influence on students' literacy skills compared to previous learning.